First Total Synthesis, Structure Revision, and Natural History of the Smallest Cytochalasin: (+)‐Periconiasin G. Issue 43 (9th September 2016) - Zaghouani, Mehdi; Kunz, Caroline; Guédon, Laura; Blanchard, Florent; Nay, Bastien
Abstract: The total synthesis of the smallest cytochalasin isolated so far, periconiasin G, which bears a seven‐membered ring in lieu of the usual macrocycle, has been performed from both enantiomers of citronellal, relying on an intramolecular Diels–Alder reaction in favor of the natural endo stereochemistry. We show that, among the four synthesized stereoisomers, including the exo isomers, the one matching the NMR data of the natural product was not that assigned in the original report, imposing structure revision. The natural product, previously isolated from a plant‐mutualistic fungus, was biologically investigated taking into account its natural history, showing significant effects against the phytopathogenic fungus Botrytis cinerea and thus opening new opportunities in combating this pest. Abstract : The total synthesis of the smallest cytochalasin isolated so far, periconiasin G, is presented. Thanks to the synthesis of four stereoisomers, comparison of data with the isolation report revealed a misassignment, imposing structure revision. Biological investigations showed significant effects against the phytopathogenic fungus Botrytis cinerea, and suggest a potential role of this compound in the mutualistic relationship between the fungal producer and its host plant.